The Influence of Social Media Use on Adolescents’ Understanding of Islamic Values in Jakarta - Teni Nurrita; Dicky Dwi Prakoso; Nadya Aulia; Imas Fitriana; Ming Pong (Thawalib: Jurnal Kependidikan Islam, 2026)
Social media significantly influences adolescents’ behavior during identity formation. Therefore, it is important to examine its impact on adolescents’ understanding of Islamic values in Jakarta. This study aims to analyze and determine the influence of social media use on adolescents’ understanding of Islamic values in Jakarta. A quantitative approach was employed in this research. The population consisted of 1,594,602 adolescents in Jakarta, with a sample of 100 respondents selected using the Slovin formula. Data were analyzed using SPSS version 25 through correlation and regression analyses. The results indicate a positive and significant influence of social media use on adolescents’ understanding of Islamic values. The correlation coefficient is 0.519, while the coefficient of determination (R²) is 0.270, indicating that 27% of the variation in understanding of Islamic values is explained by social media use, with the remaining 73% explained by other factors. The simple linear regression equation Y = 27.260 + 0.538X suggests that every one-unit increase in the social media usage score increases the understanding of Islamic values by 0.538 units. These findings highlight the importance of managing social media use in fostering adolescents’ religious values. In conclusion, social media use has a positive and significant effect on adolescents’ understanding of Islamic values in Jakarta, although much of this understanding is also influenced by other factors. This research provides useful insights for parents, educators, and policymakers in guiding adolescents to utilize social media in a more positive and constructive manner.